Iceland : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2006)
Over the last three years, a rapid expansion in domestic demand has dramatically widened the current account deficit in Iceland. Demand expanded faster than supply, and evidence of overheating is widespread. Monetary policy has tightened, but, until recently, the impact has been channeled primarily through the exchange rate. Despite hikes in the policy rate, increased competition in the mortgage market eased household credit conditions, and household indebtedness has surged. The financial market turbulence early in the year ended the favorable conditions that had allowed banks to fund rapid balance sheet growth.